Combination of Ionic Liquid and Sonication: a Fast, Mild and Green Way to Fabricate Europium–doped Lanthanide Nanophosphates. Issue 15 (28th September 2016) - Li, Yinyan; Lei, Ruoshan; Xu, Shiqing
Abstract: We introduced the synthesis of Eu 3+ ‐doped lanthanide nanophosphrates througha fast, green and facile sonication‐accelerated ionic liquid (IL)‐based reaction system. LnPO4 :Eu 3+ (Ln=La, Gd, Y, and Lu)nanostructures were prepared from aqueous solution of Ln(NO3 )3 ⋅6H2 O and IL‐1‐Hexyl‐3‐methylimidazoliumdihydric phosphate ([HMIM]H2 PO4 )under ultrasound irradiation without further use of organic solvents, surfactants or templates.The nanocrystals were obtained at 60 o C for0.5–1 h without high temperatureannealing.X‐ray powder diffraction, scanning electron microscopy, transmission electronmicroscopy and photoluminescence spectra were used to characterize the nanostructures.The results displayed that nanowires, nanorods, nanowirebundles and nanoparticles were obtained for LnPO4 :Eu 3+ (Ln= La, Gd, Yand Lu), respectively. The growth process of the nanostructureswas investigated based on a series of SEM studies of the products obtained at different sonication durations. [HMIM]H2 PO4 acted as reaction medium, reactant as well as morphology‐directing agent in the formation of the nanocrystals. Both sonication and [HMIM]H2 PO4 were two key factorsfor the fabrication of the well‐distributed nanoarchitectures. Photoluminescence properties of Eu 3+ ‐doped LnPO4 were also studied. Abstract : Eu 3+ ‐doped lanthanide nanophosphrates was synthesized througha fast, green and facile sonication‐accelerated ionic liquid‐based method. Nanowires, nanorods, nanowirebundles and nanoparticles were obtained for LnPO4 :Eu 3+ (Ln= La, Gd, Y and Lu), respectively. Both sonication and ionic liquidwere two key factorsfor the fabrication of the well‐distributed nanoarchitectures.Photoluminescence properties of Eu 3+ ‐doped LnPO4 were studied.